# (X-2)(X+3)(X-4) 0

**(X-2)(X+3)(X-4) 0**. Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6). Note that, since order doesn't matter for multiplication, i can still put the x + 2 polynomial on the bottom for the vertical multiplication, just as i always put the smaller number on the bottom when i was doing regular vertical multiplication with just plain numbers back in grammar school.

Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6). Note that, since order doesn't matter for multiplication, i can still put the x + 2 polynomial on the bottom for the vertical multiplication, just as i always put the smaller number on the bottom when i was doing regular vertical multiplication with just plain numbers back in grammar school. A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero.

(X-2)(X+3)(X-4) 0

A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero. Note that, since order doesn't matter for multiplication, i can still put the x + 2 polynomial on the bottom for the vertical multiplication, just as i always put the smaller number on the bottom when i was doing regular vertical multiplication with just plain numbers back in grammar school. Решите уравнение (x − 4)(x − 5)(x − 6) = (x − 2)(x − 5)(x − 6). Hence there is a factorisation in the form

### A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero.

Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6). Решите уравнение (x − 4)(x − 5)(x − 6) = (x − 2)(x − 5)(x − 6). A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero.

### A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero.

The famous equation x^2=2^x (all solutions!) Hence there is a factorisation in the form The famous equation x^2=2^x (all solutions!)

### Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).

A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero. The famous equation x^2=2^x (all solutions!) Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).

### The famous equation x^2=2^x (all solutions!)

A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero. Note that, since order doesn't matter for multiplication, i can still put the x + 2 polynomial on the bottom for the vertical multiplication, just as i always put the smaller number on the bottom when i was doing regular vertical multiplication with just plain numbers back in grammar school. Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).

### Решите уравнение (x − 4)(x − 5)(x − 6) = (x − 2)(x − 5)(x − 6).

Note that, since order doesn't matter for multiplication, i can still put the x + 2 polynomial on the bottom for the vertical multiplication, just as i always put the smaller number on the bottom when i was doing regular vertical multiplication with just plain numbers back in grammar school. A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero. Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).

### Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).

Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6). Решите уравнение (x − 4)(x − 5)(x − 6) = (x − 2)(x − 5)(x − 6). Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).

### The famous equation x^2=2^x (all solutions!)

Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6). Решите уравнение (x − 4)(x − 5)(x − 6) = (x − 2)(x − 5)(x − 6). A cleaner algebraic approach is to notice that due to the symmetry of the coefficients, if #x=r# is a zero of #x^4+x^3+x^2+x+1#, then #x=1/r# is also a zero.

### The famous equation x^2=2^x (all solutions!)

Note that, since order doesn't matter for multiplication, i can still put the x + 2 polynomial on the bottom for the vertical multiplication, just as i always put the smaller number on the bottom when i was doing regular vertical multiplication with just plain numbers back in grammar school. The famous equation x^2=2^x (all solutions!) Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).

### Hence there is a factorisation in the form

Hence there is a factorisation in the form The famous equation x^2=2^x (all solutions!) Решите уравнение (x − 2)(x − 4)(x − 6) = (x − 4)(x − 5)(x − 6).